PENERAPAN BERBAGAI DOSIS GARAM TERHADAP MUTU IKAN LELE SANGKURIANG (Clarias sp) ASAP MENGGUNAKAN METODE SMOKE CABINET - Muhlis, Ahmad; Kadirman, Kadirman; Mustarin, Amirah (Universitas Negeri Makassar, 2016)
The purpose of this research is to know the chemical and hedonic quality on catfish sangkuriang smoke with the different of concentration salt whichÂ processed using methods smoke cabinet. This study used a complete randomized design (CRD). The data analyzed using the analysis range and the further DMRT. Data processed using data on the program SPSS version 20.Parameters observed in research is water content, fat content, protein content and value hedonik catfishes sangkuriang smoke.The result showed the best treatment derived from treatment a salt concentration of 17%.either on chemical analysis and of testing hedonik